Effect of Capsular Tension Ring Implantation during Phacoemulsification on Postoperative Refraction - D. F. Belov; V. P. Nikolaenko (Oftalʹmologiâ, 2022)
Purpose. To assess refractive result of phacoemulsification (PE) with capsular tension ring (CTR) implantation.Patients and methods. In total, 37 eyes of 37 patients who underwent PE with intraocular lens (IOL) implantation were divided into 2 groups: study group (n = 18) with CTR implantation and control group (n = 19) without CTR. Optical biometry (IOL-Master 500) was performed for each patient before PE. Barrett Universal II Formula was used for IOL calculation. IOL power calculation error was assessed by comparing target refraction and final refraction measured by Topcon-8800 autorefractometer 1 month after surgery.Results. Despite almost identical preoperative values in both groups refractive result was different. Patients with CTR implantation had more hyperopic IOL power calculation error of +0.41 ± 0.52 D versus — 0.02 ± 0.54 D in the control group (p = 0.037). Refractive result in control group was more predictable (mean absolute error was 0.55 ± 0.34 D and 0.41 ± 0.30 D for groups respectively, p = 0.180).Conclusion. CTR implantation could help surgeon to perform PE in complicated cases. Nevertheless, CTR implantation could leads to hyperopic shift. To avoid refractive errors optimized A-constants could be used (118.85 for AcrySof SA60AT and 118.47 for Akreos Adapt AO).